PARADIGMA MEMBANGUN GENERASI EMAS 2045 DALAM PERSPEKTIF FILSAFAT PENDIDIKAN - Dongoran, Faisal R (TABULARASA, 2014)
The quality of a society has a strategic relationship with the world of education, primary school world, because in it there is a genuine effort on education to prepare the next generation of skilled and have the sciences with based on faith and piety to God Almighty in a broad context. Generation question is "golden generation" which is the connotation on future expectations about the presence of generations Indonesia genius and excelled in all fields of science and technology in the year 2045 to build the Homeland be a great nation, strong, and sovereign in the eyes of the world. Poverty appears logical golden generation is conscious and deliberate efforts are made through education and should be guided by the values of Pancasila as an ideology. Indonesian golden generation is the generation of genius, superior and Pancasila.